2022
DOI: 10.1021/acs.langmuir.2c00165
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Solvothermal Growth of Metal–Organic Framework Colloids for CO2 Capture Applications

Abstract: A quantitative study of the synthesis of metal–organic framework (MOF) colloids via a solvothermal growth process was demonstrated using electrospray-differential mobility analysis (ES-DMA), a gas-phase electrophoresis approach. HKUST-1, a copper-based MOF (Cu-MOF), was selected as the representative MOF of the study. The effects of the synthetic parameters, including ligand concentration (C BTC), synthetic temperature (T s), and synthetic time (t s) versus material properties of the Cu-MOF, were successfully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…[72] The crystal structures, pore structures, and the resulting physiochemical properties of CMOF particles can be effectively adjusted by controlling the reaction conditions. [73] Ban et al [74] reported the solvothermal synthesis of ZIF-78 (ZIF=Zeolitic Imidazolate Framework) microrods by dissolving Zn(NO 3 ) 2 • 6H 2 O, 2-nitroimidazole (nIm), 5-nitrobenzimidazole (nbIm), and triethylamine (TEA) in N,N-dimethylformamide (DMF) and performing the reaction at 120 °C for 48 h. The morphology and the aspect ratios can be tuned by changing the reactant concentration, the ligand concentration, and the relative molar ratio of nIm to nbIm. Unfortunately, these microrods have a length of larger than 10 microns and a width of several microns.…”
Section: Solvothermal Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…[72] The crystal structures, pore structures, and the resulting physiochemical properties of CMOF particles can be effectively adjusted by controlling the reaction conditions. [73] Ban et al [74] reported the solvothermal synthesis of ZIF-78 (ZIF=Zeolitic Imidazolate Framework) microrods by dissolving Zn(NO 3 ) 2 • 6H 2 O, 2-nitroimidazole (nIm), 5-nitrobenzimidazole (nbIm), and triethylamine (TEA) in N,N-dimethylformamide (DMF) and performing the reaction at 120 °C for 48 h. The morphology and the aspect ratios can be tuned by changing the reactant concentration, the ligand concentration, and the relative molar ratio of nIm to nbIm. Unfortunately, these microrods have a length of larger than 10 microns and a width of several microns.…”
Section: Solvothermal Synthesismentioning
confidence: 99%
“…One example is the MOF‐5, synthesized by Yaghi's team through the solvothermal route, which remains stable at 500 °C [72] . The crystal structures, pore structures, and the resulting physiochemical properties of CMOF particles can be effectively adjusted by controlling the reaction conditions [73] . Ban et al [74] .…”
Section: Synthesis Of Mof Particlesmentioning
confidence: 99%
“…5 Numerous methods have been discovered for modifying the structural and functional features of MOFs, which have been the target of research. 6 These synthesis techniques, such as solvothermal, [7][8][9] microwave-assisted, [10][11][12][13] mechanochemical, [14][15][16] and others, have proven essential for synthesizing MOFs with certain properties appropriate for specific uses. 17 Designing MOFs with specific pore sizes, shapes, and functions is made possible by their capacity to modify the metal and organic components, which allows for the fine-tuning of their physical as well as chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The global concern over climate change and the urgent need to mitigate greenhouse gas emissions have highlighted the importance of carbon capture and utilization (CCU) technologies. CCU not only helps in reducing emissions of CO 2 (i.e., the major greenhouse gas) but also presents opportunities for the production of valuable chemicals and fuels simultaneously. ,, As such, the development of efficient CCU processes is critical in addressing the challenges of climate change and transitioning to a more sustainable future in chemical engineering. , …”
Section: Introductionmentioning
confidence: 99%